The effect of kinds and concentration of cryoprotectant and thawing methods on frozen semen of Arab chicken - Sofjan Iskandar; Rufika Mardalestari; Resmi Hernawati; Enok Mardiah; Endang Wahyu (Indonesian Center for Animal Research and Development (ICARD), 2006)
The success of freezing chicken semen is the hope for preserving Indonesian native chickens. Semen from twenty Arab roosters were collected using massage technique once in a week. Cryoprotectant DMA (dimethyl acetamide) or DMF (dimethyl formalmide) of 7 or 9% and thawing A at temperature of 30oC for 30 seconds or in B at 5oC for 5 minutes. The volume of fresh semen was 0.3 ± 0.072 ml/ejaculate, white colour, rather thick to thick, with 2200 ± 372 millions sperms/ml and pH 6.95 ± 0.32, 4+/3+ mass movement, 80% motility, 84 ± 4.48% and abnormality of 14.75 ± 1.28%. There were not statistically significant (P>0.05) effect of interaction of treatments (kinds and concentrations of cryoprotectant, and thawing methods) on motility and live-sperms. Sperm motility preserved with DMA (34.69%) significantly higher than with DMF (29.84%). Sperm motility was also significantly higher (34.53%) when preserved with 7% cryoprotectant than with 9% (30%). Thawing-A significantly gave higher motility (35.31%) than thawing-B did (29.22%). Live-sperms of semen preserved with DMA (46.75%) was significantly higher than with DMF (41.72%). Cryoprotectant concentration of 7% gave higher live-sperms (46.98%) than of 9% did (41.48%). Thawing-A left live-sperms of 47.14%, which was significantly higher than thawing-B did (41.30%). Key Words: Frozen Semen, Arab Rooster, Cryoprotectants, Thawing Methods